2015
DOI: 10.1051/0004-6361/201526085
|View full text |Cite
|
Sign up to set email alerts
|

Rotation period distribution of CoRoT andKeplerSun-like stars

Abstract: Aims. We study the distribution of the photometric rotation period (P rot ), which is a direct measurement of the surface rotation at active latitudes, for three subsamples of Sun-like stars: one from CoRoT data and two from Kepler data. For this purpose, we identify the main populations of these samples and interpret their main biases specifically for a comparison with the solar P rot . Methods. P rot and variability amplitude (A) measurements were obtained from public CoRoT and Kepler catalogs, which were co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Thus, in the last decade, it has been possible to retrieve the rotation periods of thousands of stars (e.g. McQuillan et al 2013;Nielsen et al 2013;Walkowicz and Basri 2013;McQuillan et al 2014;Leão et al 2015).…”
Section: Photospheric Rotation From the Study Of The Photometric Lighmentioning
confidence: 99%
“…Thus, in the last decade, it has been possible to retrieve the rotation periods of thousands of stars (e.g. McQuillan et al 2013;Nielsen et al 2013;Walkowicz and Basri 2013;McQuillan et al 2014;Leão et al 2015).…”
Section: Photospheric Rotation From the Study Of The Photometric Lighmentioning
confidence: 99%
“…Thanks to the photometric observations carried out by the CoRoT (Baglin et al 2009) and Kepler (Borucki et al 2010) missions, different studies have revealed new insights on the rotation of main-sequence stars (e.g. ;De Medeiros et al 2013;Nielsen et al 2013;McQuillan, Mazeh & Aigrain 2014;Leão et al 2015;Paz-Chinchón et al 2015;Davenport 2017;Reinhold & Hekker 2020), as well as in advanced stages of stellar evolution (e.g. Mosser et al 2012;Van Saders & Pinsonneault 2013;De Medeiros et al 2013;Costa et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rotation and activity Several thousands of light-curves obtained with CoRoT and Kepler have revealed the signature of rotational modulation attributed to starspots [40][41][42][43][44]. In addition to providing a measurement of the rotational period free of the sin i projection factor, these light-curves revealed that the signature of activity is not only found in late F-G stars, for which magnetic fields and starspots were expected as in the Sun, but also in intermediate A and B type stars [45][46][47].…”
Section: Specificity Of Time Domain Informationmentioning
confidence: 99%